Gambaran Perilaku Mahasiswa dalam Pencegahan Penularan Corona Virus 2019 Disease (Covid-19) - Ronasari Mahaji Putri; Novita Dewi; Neni Maemunah (Universitas Baiturrahim, 2021)
The spread of covid-19 is increasingly out of control. Every individual has the potential to transmit covid to other humans. Various recommendations from the government for a healthy life have been made in an effort to break the chain of transmission, however it is not easy to change people's behavior into healthy behavior. This study aims to determine the description of student behavior in the prevention of covid transmission 19. This study is a descriptive study of 110 students residing in the FIKES dormitory of X University, taken using simple random sample technique. Variables are student behavior. The instrument used was a questionnaire distributed with the help of Google forms. Data analysis uses univariate test. The results showed that the majority of students namely 57 people (52.8%) had a co-19 prevention behavior with a very bad category. It is recommended that researchers further provide health education to students about clean and healthy living behaviors related to co-19 prevention, given that co-19 transmission is increasingly widespread and has become an epidemic in the world